Examining the impact of green technological specialization and the integration of AI technologies on green innovation performance: evidence from China - Khunakornbodintr, Sirinant (Frontiers in Artificial Intelligence, 2024)
China’s commitment to achieving carbon neutrality by 2060 has sparked scholars’ interest in examining the environmental ramifications of green technologies in the digital era. However, little attention has been paid to firms’ green and AI technological recombination strategies, which can significantly impact the pace of net-zero transitions. Moreover, the influence of green specialization on enterprise green innovation performance remains unclear in Chinese contemporary contexts. To address these gaps, this study investigates the moderating effect of technological specialization on the relationship between green-AI technological distance, which signifies the extent to which AI technologies have been integrated into green technologies, and enterprises’ innovation performance. Using Chinese enterprises' patent data from 2011 to 2020 and the fixed-effect regression model, the findings indicate that enterprises’ green innovation performance significantly improves as the technological distance between green and AI domains decreases. Shorter technological distance facilitates the acquisition of green technological advantages and fosters the generation of AI patents alongside green technologies. Interestingly, specialized green-technological enterprises demonstrate superior performance in integrating distant AI technologies. This occurrence could potentially be driven by the governments’ incentives and the organization’s risk attitudes, shaping green innovation outcomes. This study underscores the importance of considering technological distance and specialization in shaping innovation outcomes amidst green transitions.